Regional hegemony as a tool for peace : an evaluation of South Africa’s role in regional development - Mandela, Babongile Thabile (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science. International Studies))--University of Stellenbosch, 2010.